Liquidity, leverage, and Lehman: A structural analysis of financial institutions in crisis - Chen, Ren-Raw; Chidambaran, N.K.; Imerman, Michael B.; Sopranzetti, Ben J. (Journal of Banking & Finance, 2014)
This paper presents a flexible, lattice-based structural credit risk model that uses equity market information and a detailed depiction of a financial institution’s liability structure to analyze default risk. The model is applied to examine the term structure of default probabilities for Lehman Brothers prior to its demise. The results indicate, as early as March, that the firm would likely lose access to external capital within two years. The model can be used as both a diagnostic tool for the early detection of financial distress and a prescriptive tool for addressing the sources of risk in large, complex financial institutions.